Aktivitas antibakteri ekstrak dan fraksi makroalga Eucheuma cottoni terhadap bakteri penyebab jerawat - Kurnia, Dewi; Suhardiman, Aris; Nurdiansyah, Hedy; Ghazali, Mursal (Universitas Muhammadiyah Mataram, 2022)
Acne is a skin disease that often occurs in adolescence and even adulthood, characterized by the presence of blackheads, papules, pustules, nodes, and cysts on the face, neck, upper arms, chest, and back. Although not life-threatening, acne can affect a person's quality of life by giving a bad psychological effect in the way a person assesses, perceives and responds to his condition and situation. The aim of this study is to asses the antibacterial activity of the extract and fraction of the macroalgae Euchema cottonii against acne-causing bacteria, namely Propionibacterium acnes and Staphylococcus epidermidis. The extraction method used was maceration, using 96% p.a ethanol as a solvent and fractionation using the ECC method with three solvents with different polarity levels, namely n-hexane, ethylacetate and ethanol. The activity test was carried out using the paper disc and micro dilution method with the comparison antibacterial clindamycin. The results showed that there was no antibacterial activity from either the extract or fraction of macroalgae Euchema cottonii against the bacteria Propionibacterium acnes, but there are activity from the extract and fraction (n-hexane and ethylacetate) against the Staphylococcus epidermidis bacteria with the MBC value at a concentration of 15% and MIC at a concentration of 5% (for the extract and n-hexane fraction), while for the ethylacetate fraction the MIC value was at a concentration of 10%. Therefor, the strength of the antibacterial activity of the extract and fraction of Eucheuma cottoni is in the weak category.